Sodium alendronate is an effective adjunctive therapy for treating periodontitis in male rats treated with anticancer chemotherapy - Oliveira, Fred Lucas Pinto [UNESP]; Matheus, Henrique Rinaldi [UNESP]; Ervolino, Edilson [UNESP]; Novaes, Vivian Cristina Noronha [UNESP]; Piovezan, Bianca Rafaeli [UNESP]; Furquim, Elisa Mara de Abreu [UNESP]; Fiorin, Luiz Guilherme [UNESP]; de Almeida, Juliano Milanezi [UNESP] (Elsevier, 2023)
Objectives: To assess sodium alendronate as a local adjunctive therapy for treating experimental periodontitis in male rats treated with chemotherapy. Design: One-hundred-eighty male rats were randomly divided into two groups (n = 90) based on the systemic treatments: PSS, physiological saline solution; and 5-Fluorouracil, and then, subdivided into three subgroups (n = 30): NT, no treatment; scaling and root planing; and sodium alendronate. Treatments were performed 7 days after induction of experimental periodontitis. Specimens were collected at 14, 22, and 37 days after induction. Alveolar bone level, percentage of bone in the furcation, percentage of non-vital bone in the furcation, histopathologic features, and immunolabeling pattern for tartrate-resistant acid phosphatase (TRAP) and osteocalcin (OCN) were evaluated. Results: The lowest amount of alveolar bone and highest amount of non-vital bone was found in group 5-Fluorouracil when no treatment was performed. In animals receiving 5-Flurouracil and subjected to periodontal treatment, adjunctive sodium alendronate resulted in higher percentage of bone in the furcation and higher alveolar bone loss, when compared with scaling and root planing alone. Better structural and cellularity patterns were found in the periodontal tissues when sodium alendronate was used, regardless of systemic treatment. Higher TRAP-expression was found when no treatment was performed. Sodium alendronate didn't affect the immunolabeling pattern of osteocalcin in the presence of 5-Fluorouracil. Conclusion: Adjunctive therapy with local sodium alendronate prevented alveolar bone loss and improved the histopathological features of the periodontal tissues following scaling and root planing in male rats with experimental periodontitis receiving anticancer chemotherapy with 5-Fluorouracil.
Keywords: Alendronate; Alveolar bone loss; Antineoplastic agents; Periodontal therapy